2009
DOI: 10.1523/jneurosci.4400-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Functional Complementation ofGlra1spd-ot, a Glycine Receptor Subunit Mutant, by Independently Expressed C-Terminal Domains

Abstract: The oscillator mouse (Glra1 spd-ot ) carries a 9 bp microdeletion plus a 2 bp microinsertion in the glycine receptor ␣1 subunit gene, resulting in the absence of functional ␣1 polypeptides from the CNS and lethality 3 weeks after birth. Depending on differential use of two splice acceptor sites in exon 9 of the Glra1 gene, the mutant allele encodes either a truncated ␣1 subunit (spd ot -trc) or a polypeptide with a C-terminal missense sequence (spd ot -elg). During recombinant expression, both splice variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 46 publications
1
52
0
Order By: Relevance
“…The reduced glycine sensitivity was only partly compensated by co-expressing the ␤ wild type subunit. This result strongly suggests that the truncated subunit is incorporated into functional receptors, which is unexpected given that previous GlyR studies indicated that TM4 deletion is incompatible with the surface expression of functional ␣1 GlyRs (32)(33)(34)(35). Given our unexpected result, we sought to confirm whether the p.E375X mutant subunit was incorporated into functional GlyRs using voltage clamp fluorometry.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The reduced glycine sensitivity was only partly compensated by co-expressing the ␤ wild type subunit. This result strongly suggests that the truncated subunit is incorporated into functional receptors, which is unexpected given that previous GlyR studies indicated that TM4 deletion is incompatible with the surface expression of functional ␣1 GlyRs (32)(33)(34)(35). Given our unexpected result, we sought to confirm whether the p.E375X mutant subunit was incorporated into functional GlyRs using voltage clamp fluorometry.…”
Section: Resultsmentioning
confidence: 63%
“…We also attempted to confirm it using immunofluorescence, but the incorporation rate may have been too low to allow surface expression to be detected. As noted above, we were surprised that the p.E375X subunit was incorporated, given that previous studies have shown that TM4 deletion is incompatible with the surface expression of functional ␣1 GlyRs (32)(33)(34)(35). Indeed, the deletion of only a few residues at the C-terminal end of the TM4 domain is sufficient to render some pLGIC receptors completely nonfunctional (12,44,45).…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, additional dominant and recessive inheritance patterns and compound heterozygosity have been described for other patient families in which various GLRA1 missense or null mutations have been identified (4,5,97). Some of these mutations have been found to affect GlyR intracellular trafficking rather than agonist binding or channel gating (69,98). Consistent with an important role of the ␤ subunit in postsynaptic GlyR function, mutations in the GLRB gene have been associated with HKPX2 (97,99).…”
Section: Mutations In Human Glyr Genes Cause Hyperekplexiamentioning
confidence: 99%
“…These regions also influence receptor expression : the number and characteristics of C-terminal residues in M4 are critical for the expression of 5-HT 3 R on the cell surface (Butler et al 2009) and the expression of non-assembling receptors that contain only the ECD and M1-M3 helices can be rescued by co-expression with M4 (Haeger et al 2010 ;Villmann et al 2009). Thus, the M3 and M4 regions are an integral part of the receptor, and have a function that extends beyond simply shielding M2 from the membrane.…”
Section: M3 and M4 Helicesmentioning
confidence: 99%